2007
DOI: 10.1111/j.1574-6968.2006.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of total bacterial and ammonia-oxidizing bacterial community composition in a full-scale aerated submerged biofilm reactor for drinking water pretreatment in China

Abstract: The community composition of total bacteria and ammonia-oxidizing bacteria in a full-scale aerated submerged biofilm reactor for drinking water pretreatment was characterized by analysis of 16S rRNA gene and the functional gene amoA, respectively. Sampling was performed in February and in July. 16S rRNA gene clone libraries revealed 13 bacterial divisions. At both sampling dates, the majority of clone sequences were related to the Alpha- and Betaproteobacteria. A minor proportion belonged to the following grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Chloroflexi phylotypes have also been found in abundance in artificial and engineered ecosystems, such as lagoons (e.g., (97)), mine drainage (e.g., (73,79)), anaerobic sludges for waste and wastewater treatment (e.g., (2,12,17,19,25,30,43,51,57,58,64,66,71,74,76,90,94)), activated sludge systems (e.g., (3,8,13,25,42,45,47,55,56,60,62,77,80,98)), and microbial fuel cell systems (39,61). Among these ecosystems, waste/wastewater treatment facilities are perhaps the best-recognized habitat where Chloroflexi phylotypes reside in abundance.…”
Section: Special Issuementioning
confidence: 99%
“…Chloroflexi phylotypes have also been found in abundance in artificial and engineered ecosystems, such as lagoons (e.g., (97)), mine drainage (e.g., (73,79)), anaerobic sludges for waste and wastewater treatment (e.g., (2,12,17,19,25,30,43,51,57,58,64,66,71,74,76,90,94)), activated sludge systems (e.g., (3,8,13,25,42,45,47,55,56,60,62,77,80,98)), and microbial fuel cell systems (39,61). Among these ecosystems, waste/wastewater treatment facilities are perhaps the best-recognized habitat where Chloroflexi phylotypes reside in abundance.…”
Section: Special Issuementioning
confidence: 99%
“…The findings of Green and Lytle were based primarily on culture-dependent methods, with little use of culture-independent (molecular) methods by Green (C. N. Green, presented at Rice University, Houston, TX, 19 October 2007) (18,19). Molecular microbiological techniques used to characterize microbial communities in wastewater processes are a well-studied field; however, characterization of full-scale, biologically active water treatment systems for drinking water is limited (16,25,26,36,38). There is a clear need to better identify the diversity of bacterial communities, including the presence of human pathogens, in biologically active drinking water filters to improve the understanding of such a complex system.…”
mentioning
confidence: 99%
“…Nitrosomonas nitrosa like sequences have often been isolated from systems with high ammonia concentration such as industrial wastewater treatment plants (Dionisi et al, 2002) and at the same time from low ammonia environments such as freshwater estuaries (Cebron et al, 2003) and a submerged biofilm for drinking water pretreatment in China (Qin et al, 2007). Nitrosomonas nitrosa-like sequences were abundant in the wetland cell 1 which receives highly variable NH 3 -N concentrations, corroborating the claims of ecological versatility for this group.…”
Section: Figurementioning
confidence: 61%
“…therefore Nitrosospira spp would be more likely to predominate in low ammonia environments (Schramm et al, 1996) and may be better at withstanding physicochemical variations (Purkhold et al, 2000). However, these findings are just indicative as other studies of systems receiving low ammonia waters (Qin, et al 2007;Regan et al, 2002) revealed that Nitrosomonas-like sequences were predominant over Nitrosospira-like sequences. Our T-RFLP results support the sequence data.…”
Section: Figurementioning
confidence: 85%
See 1 more Smart Citation